Switch lists in the landscape of knowledge representation languages - Ondrej Cepek (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
A switch-list representation (SLR) of a Boolean function is a compressed truth table representation of a Boolean function in which only the function value of the first row in the truth table and an ordered list of switches are stored. A switch is a Boolean vector whose function value differs from the value of the preceding Boolean vector in the truth table. In this short paper we outline scenarios under which SLRs constitute a better representation language than standard representation languages such as CNFs and OBDDs. Furthermore, we outline a possible approach to constructing a compiler from CNFs to SLRs which is a necessary tool for verifying practical usefulness of SLRs.